2020
DOI: 10.1002/dneu.22771
|View full text |Cite
|
Sign up to set email alerts
|

Axo‐glial interaction in the injured PNS

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 155 publications
(255 reference statements)
0
30
0
Order By: Relevance
“…After this initial regression to the progenitor-like cell, SCs activate different molecular mechanisms to eventually transform into the regeneration-supporting phenotype. Through this process, SCs will acquire the new identity of repair SCs [ 10 , 20 , 21 , 22 , 23 , 24 ]. The regression to a progenitor-like cell phase is characterized by a reversal of all developmental steps that assist SCs during the functional acquisition of tools for proper interactions with axons.…”
Section: Phase One: Detachment From Degenerating Axons—denervationmentioning
confidence: 99%
See 2 more Smart Citations
“…After this initial regression to the progenitor-like cell, SCs activate different molecular mechanisms to eventually transform into the regeneration-supporting phenotype. Through this process, SCs will acquire the new identity of repair SCs [ 10 , 20 , 21 , 22 , 23 , 24 ]. The regression to a progenitor-like cell phase is characterized by a reversal of all developmental steps that assist SCs during the functional acquisition of tools for proper interactions with axons.…”
Section: Phase One: Detachment From Degenerating Axons—denervationmentioning
confidence: 99%
“…Of the three members of the neuregulin-1 family, NRG-1 type III plays an essential role in SC proliferation, differentiation and myelination during development and in the remyelination of regenerating nerves [ 24 , 46 , 48 , 115 ]. Interestingly, in vivo experiments in mice after severe crushed nerve lesions demonstrated that an overexpression of NRG-1 type III can restore the correct thickness of myelin.…”
Section: Phase Four: Contact With Regrowth Axonsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanisms of Schwann cell remyelination share similarities to myelination during development, however there are also notable differences (Stassart & Woodhoo, 2020). Given the role of class II a HDACs in myelination we asked whether they are also involved in remyelination after nerve injury.…”
Section: Remyelination Kinetics Depends On Class Iia Hdac Gene Dosementioning
confidence: 99%
“…After axon regeneration Schwann cells reestablish contact with them and downregulate c-Jun. This allows re-expression of Krox20 and the consequent reactivation of a gene expression program aimed at remyelination of axons and reestablishment of nerve function (Stassart & Woodhoo, 2020). Activation of Gpr126, a G-protein-coupled receptor that increases intracellular levels of cAMP, is required for Schwann cell myelination and remyelination (Monk et al, 2009(Monk et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%